Migration and gout: the Tokelau Island migrant study. Issue 6596 (22nd August 1987) - Prior, I A; Welby, T J; Ostbye, T; Salmond, C E; Stokes, Y M
Abstract : The prevalence and 14 year incidence of clinical gout and its precursors were investigated in the Polynesian population of Tokelauans living in the Pacific basin, non-migrant Tokelauans living in their isolated atoll homeland being compared with migrant Tokelauans living in urban New Zealand. The age standardised prevalence of gout in Tokelauan men in New Zealand was higher than that in non-migrant Tokelauan men, being 21.0 and 19.5/1000 subjects at the beginning of the study and 51.0 and 14.6/1000 at the end of study, respectively. Migrant men in New Zealand aged under 55 had higher mean serum uric acid concentrations than non-migrant men of the same age. The prevalence of gout was low in women in both environments. The age standardised relative risk of developing gout between 1968 and 1982 was 9.0 times higher in the migrant men than in the non-migrant men. Age, serum uric acid concentration, serum cholesterol concentration, and self reported alcohol consumption at entry to the study were the best set of predictors of gout in men. Preventive strategies to change body mass, diet, and patterns of alcohol use need to be developed in this population.